MORPHOLOGICAL ASSESSMENT OF THE REGENERATION OF THE PERIODONTAL LIGAMENTUM IN THE TREATMENT OF GENERALIZED PERIODONTITIS WITH PLASMOGEL FROM PLATELY AUTOPLASMA - Vishnevskaya, A.A.; Schnayder, S.A.; Reyzvikh, O.E.; Babenya, A.A.; Khrystova, M.T. (World of Medicine and Biology, 2020)
The purpose of the investigation was to study the effect of Plasmogel from platelet autoplasma on the regeneration of collagen fibers of the periodontal ligament in an experimental study on rats with a ligature model of periodontitis. The animals were divided into 2 groups: the first – control of the healing of the pathology without treatment, the second – experimental. For morphological examination, tissue biopsies were taken, Mallory staining was used to determine the fibrous structures of connective tissue. On visual inspection, healing occurred in both groups. However, it didn't go the same way. In Group I, visual recession was noted. In Group II, the recession was not visually identified. In Group I of animals, signs of a chronic inflammatory process were detected, and stromal fibrosis was revealed. The largest area occupied by collagen fibers in the periodontal ligament was recorded in Group II of animals, which is 61.93%. In Group I animals, indicator of the area of collagen fibers significantly lower – 35.44%. Plasmogel is used to create a framework and microenvironment for the growth of collagen fibers of the periodontal ligament, which increases the regenerative capabilities.
Keywords: biomaterials; periodontitis; ligature model; plasma therapy; collagen fibers